Histopathologic spectrum of cystic ovarian masses - Ranabhat, S; Tiwari, M; Maharjan, S; Bhandari, A; Subedi, M; Osti, B P (Journal of Chitwan Medical College, 2017)
This research was a cross sectional analytic observational histopathological study of cystic ovarian lesions carried out over three years from March, 2012 to February, 2015 at Chitwan Medical College Teaching Hospital in Nepal. The objective of this study was to study cystic ovarian masses histopathologically. A total of one hundred and fourteen patients with cystic ovarian masses were included into the study. 46.5% lesions were non-neoplastic (83% physiologic and 17% pathologic) and 53.5% lesions were neoplastic (91.8% benign and 8.2% malignant). Follicular cyst was the most common ovarian cystic lesion overall, followed by mature cystic teratoma and serous cystadenoma. 14.9% of all the ovarian cysts had undergone torsion; among them mature cystic teratoma was the most common lesion to have undergone the complication. Neoplastic ovarian cysts were more common than non-neoplastic. Follicular cyst was the most common ovarian cyst overall. Mature cystic teratoma was the ovarian cystic lesion to be affected by torsion most commonly.